Memory and mastery : Primo Levi as writer and witness - Kremer, Roberta S., 1946- (SUNY series in modern Jewish literature and culture., 2001)
Eleven essays representing diverse approaches--literary, psychoanalytic, linguistic, and historical--focus on all aspects of Italian writer and Holocaust survivor Levi's oeuvre, including his science-fiction writings and his poetry, as well as his fictional and nonfictional writings about the Holocaust. According to editor Kremer of the Vancouver Holocaust Education Centre, Holocaust literature has not made many inroads into mainstream literary criticism, because respect for the subject matter tends to over-ride consideration of the writer's means of expression. These essays begin a look at Levi's writing through analysis of genre, audience, discourse, canon formation, reader reaction language, and form. Annotation copyrighted by Book News Inc., Portland, OR.